KONSEP BARU PENDIDIKAN KARAKTER MABADI KHAIRA UMMAH - Agus Salim Chamidi (IAINU Kebumen, 2019)
Article is about a new concept of character education mabadi khaira ummah (MKU). The concept tries to integrate concept of character education with unique concept mabadi khaira ummah (MKU). The aim is to develop an unique concept based on socio-cultural Indonesia having Bhinneka Tunggal Ika in Islamic prespective. This new concept rests on concepts and values khaira ummah, ummatan wasathan, and rahmatan lil ‘alamin. Its orientation is building noble character personal individually and socially for our students with the dimensions of living in the world at now and the hereafter